Answer:
The roots of the function are x = -5/3 and 3. Select these.
Step-by-step explanation:
The roots of the function are the solutions to the function. They are also called the x-intercepts or zeros. To find them, factor the function completely and solve using the zero product property.
f(x) = (3x+5)(x2-6x+9)2 becomes f(x) = (3x+5)(x-3)^2
Set each factor equal to 0 and solve for x.
(3x+5)=0
3x = -5
x = -5/3
(x-3)^2 = 0
x - 3=0
x = 3
Let's call the number you thought of n. Then what the two steps you took can be written as an equation:
![n+4\frac{5}{7}=12n](https://tex.z-dn.net/?f=n%2B4%5Cfrac%7B5%7D%7B7%7D%3D12n)
Subtract n to get all of your variables to one side:
![4\frac{5}{7}=11n](https://tex.z-dn.net/?f=4%5Cfrac%7B5%7D%7B7%7D%3D11n)
At this point, I recommend turning your mixed number into an improper fraction. It will make things easier later on:
![\frac{33}{7}=11n](https://tex.z-dn.net/?f=%5Cfrac%7B33%7D%7B7%7D%3D11n)
Now divide both sides by 11 to get the value of n:
P^-4 x -5p
In properties of exponents, if the exponent is negative then you move the variable with the negative exponent to the denominators place and it changes to positive and the numerator becomes 1.
p^-4=1/(p^4)
Also, if no exponent is present it is understood to be 1.
Keeping this in mind,
p^-4 x -5p
1/(p^4) x -5p^1 substituted p^-4 by 1/p^4 and added ^1 to -5p
-5p^1/p^4 multiplied-5p^1 to 1
-5/p^3 simplified
Answer:
-1/24
Step-by-step explanation:
-7/8 - (-5/6)
Subtracting a negative is like adding
-7/8 + 5/6
Get a common denominator
-7/8 * 6/6 + 5/6 *8/8
-42/48 + 40/46
-2/48
-1/24